2014
DOI: 10.3109/17435390.2014.948941
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic effects of nano- and bulk-TiO2 particles in the soil nematode Caenorhabditis elegans

Abstract: The toxicity and toxicogenomics of selected anatase and rutile nanoparticles (NP) and bulk titanium dioxide (TiO2) particles were evaluated in the soil nematode Caenorhabditis elegans. Results indicated that bulk or nano-TiO2 particles were slightly toxic to soil nematode C. elegans, as measured by reproduction EC50 values ranging from 4 to 32 mg/L. Whole-genome microarray results indicated that the regulation of glutathione-S-transferase gst-3, cytochrome P450 cypp33-c11, stress resistance regulator scl-1, ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Induction of different C. elegans CYPs after NP exposure was observed after treatment of C. elegans with Fe 2 O 3 -, TiO 2 - and CeO 2 -NPs. [47, 70, 103]…”
Section: Biological Responses Triggered By Metal and Metal Oxide Nmentioning
confidence: 99%
“…Induction of different C. elegans CYPs after NP exposure was observed after treatment of C. elegans with Fe 2 O 3 -, TiO 2 - and CeO 2 -NPs. [47, 70, 103]…”
Section: Biological Responses Triggered By Metal and Metal Oxide Nmentioning
confidence: 99%
“…The fast phenotyping of C. elegans can be coupled with transcriptome profiling (i.e., gene expression microarray or RNAseq) to study underlying molecular mechanisms. For instance, using gene expression microarray, Rocheleau et al found that C. elegans exposed to nano-TiO 2 showed increased expression of the glutathione S-transferase gene gst-3 and the cytochrome P450 gene cyp33-11; while the oxidative stress response, as measured by the stress resistance regulator scl-1, showed increased expression after exposure to both nano-and bulk-sized TiO 2 (Rocheleau et al, 2015). In addition, the expression of pod-2, a reproduction-related gene, was decreased in a concentration-dependent manner with nano-TiO 2 exposure (Rocheleau et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, using gene expression microarray, Rocheleau et al found that C. elegans exposed to nano-TiO 2 showed increased expression of the glutathione S-transferase gene gst-3 and the cytochrome P450 gene cyp33-11; while the oxidative stress response, as measured by the stress resistance regulator scl-1, showed increased expression after exposure to both nano-and bulk-sized TiO 2 (Rocheleau et al, 2015). In addition, the expression of pod-2, a reproduction-related gene, was decreased in a concentration-dependent manner with nano-TiO 2 exposure (Rocheleau et al, 2015). Based on the same technology, Starnes et al identified that five lysosomal pathway related genes, including genes encoding the cysteine proteases cpr-1 and cpr-2, were changed significantly after exposure to silver (Ag) nanoparticles (Starnes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…C. elegans exposed to TiO 2 and CeO 2 -NPs. (Roh et al, 2010a, Helvenstein et al, 2015, Rocheleau et al, 2015, Iavicoli et al, 2016 NP-induced responses on protein processing and proteasome have been previously linked to nanotoxicity of inorganic nanoparticles. In particular, Scharf et al found that protein homeostasis was a major target of SiO 2 -NPs.…”
Section: Study Of Lipid Oxidationmentioning
confidence: 99%
“…, Gonzalez-Moragas et al, 2015a Several toxicogenomic studies have provided evidence that titanium oxide, gold and silver nanoparticles induce nanotoxic mechanisms in C. elegans. (Tsyusko et al, 2012, Rocheleau et al, 2015, Starnes et al, 2016 However, further research on different NP composition, sizes and surface properties is required to correlate the physicochemical properties of the materials with the molecular effects. Starnes et al examined the toxicogenomic responses of pristine Ag-NP, sulfidized Ag-NPs, and AgNO 3 in C. elegans.…”
Section: Introductionmentioning
confidence: 99%